2019
DOI: 10.1001/jamaoncol.2019.3323
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-effectiveness Analysis of Multigene Testing for All Patients With Breast Cancer

Abstract: IMPORTANCE Moving to multigene testing for all women with breast cancer (BC) could identify many more mutation carriers who can benefit from precision prevention. However, the cost-effectiveness of this approach remains unaddressed. OBJECTIVE To estimate incremental lifetime effects, costs, and cost-effectiveness of multigene testing of all patients with BC compared with the current practice of genetic testing (BRCA) based on family history (FH) or clinical criteria. DESIGN, SETTING, AND PARTICIPANTS This cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
137
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(141 citation statements)
references
References 70 publications
4
137
0
Order By: Relevance
“…28 The costs for mammography, MRI, and prophylactic procedures were derived from published sources. 13 , 27 Cancer costs were assessed for the first year of treatment, for continuing treatment in subsequent years, and as palliative therapy for the last year of life. 27 We assumed that the transition to death from any 1-year or after cancer health state incurred palliative treatment costs.…”
Section: Methodsmentioning
confidence: 99%
“…28 The costs for mammography, MRI, and prophylactic procedures were derived from published sources. 13 , 27 Cancer costs were assessed for the first year of treatment, for continuing treatment in subsequent years, and as palliative therapy for the last year of life. 27 We assumed that the transition to death from any 1-year or after cancer health state incurred palliative treatment costs.…”
Section: Methodsmentioning
confidence: 99%
“…As per national guidelines, in some subgroups (e.g., Ashkenazi Jewish heritage), all women with breast cancer are recommended to undergo genetic testing. 13,29 Of note, a recent paper considered the cost-benefit ratio of multigene panel testing for all breast cancer patients 31 and while the modeling results might be overly optimistic, these types of efforts are crucial in generating data to inform testing practices.…”
Section: Evidence-based Screening For Cancer Patientsmentioning
confidence: 99%
“…One approach is diagnosis-based testing, for example, test all patients with breast cancer. 7,14,15 The American Society of Breast Surgeons (ASBS), for example, endorses testing for all patients with breast cancer that includes at least BRCA1, BRCA2, and PALB2. 14 A second approach is population offering, that is, offering testing broadly, regardless of whether or not an individual has a personal or family history of cancer.…”
Section: Ind I C Ati On S For G Ene Tic Te S Tingmentioning
confidence: 99%
“…A follow-up analysis found the population screening approach to be more cost-effective than the family history-based approach over a range of scenarios. 15 A frequently cited concern with population testing is the potential for excess psychologic distress, although a prospective study conducted in Israel reported high satisfaction and no excess psychologic harm with a streamlined BRCA screening approach in unaffected Ashkenazi Jewish individuals. 19 With broadened testing criteria, resources will need to be directed toward access to cancer genetics services to ensure safe and effective delivery of care.…”
Section: Ind I C Ati On S For G Ene Tic Te S Tingmentioning
confidence: 99%